Recognition of Staphylococcus aureus by the pattern recognition molecules langerin, mannan-binding lectin, and surfactant protein D: the influence of capsular polysaccharides and wall teichoic acid - Hymøller, Kirstine Mejlstrup; Christiansen, Stig Hill; Schlosser, Anders Grønnegaard; Skov Sørensen, Uffe B.; Lee, Jean C.; Thiel, Steffen (Frontiers in Immunology, 2025)
The innate immune system plays a critical role in the rapid recognition and elimination of pathogens through pattern recognition receptors (PRRs). Among these PRRs are the C-type lectins (CTLs) langerin, mannan-binding lectin (MBL), and surfactant protein D (SP-D), which recognize carbohydrate patterns on pathogens. Each represents proteins from different compartments of the body and employs separate effector mechanisms. We have investigated their interaction with the Gram-positive opportunistic pathogen Staphylococcus aureus, a bacterium whose cell wall contains two key glycopolymers: capsular polysaccharide (CP) and wall teichoic acid (WTA). Using a langerin-expressing cell line and recombinant langerin, MBL, and SP-D, we demonstrated that langerin, MBL, and SP-D all recognize nonencapsulated S. aureus. However, the bacterium may produce CP that effectively shields S. aureus from recognition by all three CTLs. Experiments utilizing mutant S. aureus strains confirmed that WTA is a ligand for MBL, but that langerin likely interacts with an additional unknown ligand. A competition assay revealed that MBL and SP-D inhibit langerin’s interaction with S. aureus, highlighting the intricate redundancy and cooperation within the innate immune system. This study highlights the dynamic interplay of langerin, MBL, and SP-D in recognizing specific surface structures on S. aureus and provides insight into how this pathogen evades innate immune recognition.